2019
DOI: 10.1101/815944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Timing matters: The temporal representation of experience in subjective mood reports

Abstract: Mood is thought to integrate across our experiences, yet we do not know how the relative timing of past events shapes how we feel in the moment. Here, we investigate the relationship between the timing of previous experiences and mood by combining a novel closed-loop mood controller alongside computational modelling and neural data. We first present the development of a Mood Machine Interface which allows us to individualize rewards in real-time in order to generate substantial mood transitions, across healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…14 subjects were initially analyzed as an exploratory sample to inform the study hypotheses (as reported in our preregistration available at https://osf.io/djw8h), leaving a separate confirmatory sample of 40 subjects for analyses at the sensor level and a subsample of 37 subjects at the source level. The task consists of three blocks, where in each block a closed-loop mood controller delivers reward prediction errors to try to move the participant's mood to a target value (see (Keren et al, 2020) for details on the task design). The targets of the controller are to reach the highest (first block), lowest (second block), and then highest mood again (third block).…”
Section: Samplementioning
confidence: 99%
See 4 more Smart Citations
“…14 subjects were initially analyzed as an exploratory sample to inform the study hypotheses (as reported in our preregistration available at https://osf.io/djw8h), leaving a separate confirmatory sample of 40 subjects for analyses at the sensor level and a subsample of 37 subjects at the source level. The task consists of three blocks, where in each block a closed-loop mood controller delivers reward prediction errors to try to move the participant's mood to a target value (see (Keren et al, 2020) for details on the task design). The targets of the controller are to reach the highest (first block), lowest (second block), and then highest mood again (third block).…”
Section: Samplementioning
confidence: 99%
“…Participants rate their mood with a slider between a value of 0 and 100 (with 0 being the lowest and 100 being the highest) every 2 to 3 trials of the gambling task. Reward prediction error and expectation are estimated according to the primacy mood model proposed by (Keren et al, 2020) defining the mood at time ! as:…”
Section: Mood Modelmentioning
confidence: 99%
See 3 more Smart Citations